Experimental observation of von Kármán vortices during drop impact - Castrejón-Pita, A; Castrejón-Pita, JR; Hutchings, I (2012)
The observation of von Kármán type vortices during the impact of water droplets onto a pool of water is reported. Shadowgraph imaging and laser-sheet visualization are used to document these events. The appearance of these vortices occurs within theoretically predicted regions in a Reynolds-splash number parameter space. In addition, and also in agreement with theoretical predictions, smooth splashing, with vortices absent, is found for smaller Reynolds number. © 2012 American Physical Society.